A robust watermark embedding in smooth areas - Zeki, Akram M.; Abdul Manaf, Azizah; Adamu, Abubakar Ibrahim; Zamani, Mazdak (Academic Journals Inc., 2011)
Robustness is one of the most important properties of watermarking, the watermark should be readable from images that underwent common attacks such as lossy compression or Joint Photographic Experts Group (JPEG). While many publications consider the relation between smoothness and quality of the images, few studies only concentrate on the relation between smoothness and watermarking robustness. This study focuses on watermark robustness on different smooth areas. The effectiveness of lossy compression on different smooth intensity areas was tested, and the average of pixel value change before and after compression for each field of smoothness intensity was found to embed the watermark objects within less effective areas.